A Criticism to Sokhan Dictionary of Metonymy - Arash Amraei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The ability of the Persian language with its cultural contexts made many Persian words and expressions have different meanings and functions under different situations. Expressing the metonymy of various phrases and expressions in the Persian language is one of these functions. For this reason, metonymy has always been considered by linguists, poets, and authors as part of the language and culture of any society. Metonymy is the beautiful, artistic, and implicit expression of different topics used by poets and authors as a subtle technique in expressing their purposes. Due to the extensive use of metonymy by Persian poets and authors, the collection, analysis, and interpretation of metonymy is a critical and competent task. Hassan Anwari and his colleagues complied and published a dictionary called “Sokhan Dictionary of Metonymy,” which is analyzed in this study. This book was published in two volumes in 1783. After reviewing and evaluating different concepts related to the book, the book structure has been succinctly introduced. Then, the content analysis and evaluation of the book was done. It was found that since this culture has been extracted from discourse culture, except metonymy, some other irrelevant entries have been mixed with it, leading to some incongruities and misinterpretations. In so doing, some of the most egregious problems are enumerated. It was finally concluded that this book needs to be seriously revised and rectified.